2011
DOI: 10.1308/147870811x582792
|View full text |Cite
|
Sign up to set email alerts
|

Conservative surgery in the management of a benign ovarian cystic teratoma presenting as a rectal mass: a case report

Abstract: Ovarian cystic teratomas constitute 10-15% of all ovarian tumours and are the most common ovarian neoplasms found in adolescence and during pregnancy. Nevertheless, ovarian cystic teratomas have also been described in patients aged 1-91 years. We report an unusual case of a benign ovarian cystic teratoma presenting as a rectal mass that was managed surgically using radical resection by a multidisciplinary team. This case report highlights the importance of preoperative investigations including colonoscopy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…2,19 Many previous studies have reported that MCT could invade neighboring organs, including urinary bladder, small intestine, sigmoid colon, rectum, and transverse colon, leading to the formation of fistulas. [22][23][24][25][26][27][28][29][30][31][32][33][34] Recent studies have even concluded that MCT could be strikingly related to Anti-N-Methyl-D-Aspartate Receptor Encephalitis, a rare and understudied paraneoplastic neurological syndrome in both pregnant and non-pregnant patients. 35,36 It has been linked to adverse pregnancy outcomes, such as intrauterine growth restriction and pre-term deliveries, and could even complicate labor by obstructing the birth canal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,19 Many previous studies have reported that MCT could invade neighboring organs, including urinary bladder, small intestine, sigmoid colon, rectum, and transverse colon, leading to the formation of fistulas. [22][23][24][25][26][27][28][29][30][31][32][33][34] Recent studies have even concluded that MCT could be strikingly related to Anti-N-Methyl-D-Aspartate Receptor Encephalitis, a rare and understudied paraneoplastic neurological syndrome in both pregnant and non-pregnant patients. 35,36 It has been linked to adverse pregnancy outcomes, such as intrauterine growth restriction and pre-term deliveries, and could even complicate labor by obstructing the birth canal.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have proposed that the presence of an inflammatory response in patients with MCT leads to invasion into neighboring or distant organs. [22][23][24][25][26][27][28][29][30][31][32][33]35,36 Collectively, inflammatory responses originating from ovarian MCT sequentially involve maternal serum and ultimately the intrauterine compartment, which could possibly lead to the development of PROM.…”
mentioning
confidence: 99%
“…These account for 10% to 20% of all ovarian neoplasms. 1 These are commonly asymptomatic and are found incidentally on imaging studies performed for other indications. 2 Complications of these tumors include torsion (16%), rupture (0.5%), and malignant degeneration (2%-6%).…”
Section: Answer To Image 2 (Page 815): Mature Cystic Teratoma Of the mentioning
confidence: 99%